A role for eIF4A1 in IL-10 induction by LPS - Alam, M. Mustafa (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2014)
microRNAs are a family of short non-coding RNAs that act as fine tuners of gene expression by controlling mRNAs. They have been implicated in numerous diseases including inflammatory diseases. A number of studies have looked at differential expression in response to stimulators of innate immunity, notably the gram negative bacterial product lipopolysaccharide (LPS) which acts via toll-like receptor 4. This study initially focused on LPS-induced miRNA repression. A number of miRNAs that were LPS-repressed were identified and an analysis was performed to identify their targets and determine their role in innate immunity. Let-7c-1-3p was identified as an LPS-repressed miRNA, and was predicted to target the eukaryotic translation initiation factor eIF4A2.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin